Data on polyphenols and biological activity analyses of an Andean tomato collection and their relationships with tomato traits and geographical origin - Di Paola Naranjo, Romina Daniela (2016)
Data provide information about a tomato collection composed of accessions from the Andean Valley, commercial accessions and wild species. Antioxidant metabolites were measured inmature fruits of this collection, and their biological activities were assessed by both in vitro and in vivo methods. In this work, the parameters used to identify and quantify polyphenols compounds in tomato fruit by liquid chromatography coupled to diode array detector and quadruple time of flight mass spectrometer are described. Moreover,data supporting a procedure to characterize the properties of tomato fruits to revert death by thermal stress in Caenorhabditis elegans are explained in detail. Lastly, principal component analysis and hierarchical cluster analysis of metabolites composition, antioxidant activities (in vivo and in vitro), tomato traits and geographical origin of the tomatoes collection are shown. The data presented here are related to the research article entitled “Hydrophilic antioxidants from Andean Tomato Landraces assessed by their bioactivities in vitro and in vivo”